Studies on fiscal and monetary problems - Bose, Swadesh R. (Karachi : Pakistan Institute of Development Economics, 1970)
This volume is a collection of studies on fiscal and monetary problems in Pakistan. These studies were done at the Pakistan Institute of Development Economics in the first half of the 1960's by both national and international scholars. Some of the contribution is on fiscal problems and monetary problems especially as it concerns developing countries.
Includes bibliographical references: p. 274-275.
usc 23/06/2017
Loans
Keywords: Taxation; Fiscal policy; Monetary policy; Pakistan